PID based control of regenerative inverter for DC rail transit - Ceylan, Mahmut Cagri; Dasdemir, Janset; Dursun, Ufuk; Ustoglu, Ilker (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2023)
Purpose: In order to obtain fast respond to dynamic changes in line voltage, a new PID-based control mechanism has been proposed. In addition, it is aimed to recover more regenerative energy with the proposed operating strategy. Theory and Methods: A PID controller has been designed based on the dominant pole assignment method considering the current loop. The proposed operating strategy that considers two different voltage values, unlike the systems that operate at constant voltage value in the literature, is proposed. Results: With the proposed control mechanism, the design accuracy has been increased. The derivative effect of the PID provides fast response to these changes in line voltage by increasing the speed of the system response and the slow dynamic response of PI-based control structure has been improved. This operating strategy provides more regenerative energy recovery by increasing the inverter operation region and contributes to energy efficiency. Conclusion: A detailed model of a real system has been developed in Matlab/Simulink environment. The simulation results comparing the performance of the PID-based control structure with the PI-based control has been presented to illustrate the feasibility and efficiency of the proposed method.
Keywords: Energy efficiency; DC rail transit; Regenerative inverter; PID controller; Vector control; MODEL; Engineering